Who You Speak to Matters: Information Sharing and the Management of a Small-Scale Fishery - Obregón, Clara; Admiraal, Ryan; van Putten, Ingrid; Hughes, Michael; Tweedley, James R.; Loneragan, Neil R. (Frontiers in Marine Science, 2020)
Sustainable natural resource management requires collaboration, adaptability and coordination between science, policy and stakeholders. Communication of scientific information through social networks is integral to effective governance. This study employed social network analysis to investigate information flow between stakeholders associated with the blue swimmer crab (Portunus armatus) fishery in the Peel-Harvey Estuary, south-western Australia. Although the fishery received Marine Stewardship Council certification in 2016, a preliminary study conducted between 2017 and 2018 revealed that fishers were concerned about its status and management. Consequently, 85 face-to-face interviews were conducted with commercial and recreational fishers, academics, government bodies, representatives of fishing organizations, non-governmental organizations, and tourism organizations to understand the flow of information and the influence on perceptions of sustainability. The results showed that: i) Few individuals were key for sharing information within and between different organizations forming the fishery network and only two of the six groups (government bodies and the commercial fishing sector) were highly connected and appeared as key for information sharing; ii) After the public sector stakeholders, academic groups were the second-least connected, despite having actively researched the Peel-Harvey Estuary and the P. armatus fishery for over 40 years; iii) Recreational fishers exchanged information mainly with other fishers and the regional fisheries department, rather than the organization representing recreational fishers; iv) Modes of communication used with the recreational fishing sector greatly differed between the fisheries department (i.e., mainly via phone/email) and the recreational fishing organisation (i.e., strong online presence, social media and phone/email); v) Issues of inclusiveness and representation were highlighted for some of the groups and organizations. This study has identified logistical and institutional difficulties to communicate information regarding the science, management and environmental issues related to a small-scale crab fishery, providing managers and other stakeholders with a pathway of action for enhancing resource management.